Do nano-particles cause recalcitrant vulnerability curves in Robinia? Testing with a four-cuvette Cochard rotor and with water extraction curves. (19th May 2018) - Du, Guangyuan; Feng, Feng; Wang, Yujie; Tyree, Melvin T
Abstract: Cavitation resistance is a key trait for characterizing the drought adaption in plants and is usually presented in terms of vulnerability curves. Three principal techniques have been developed to produce vulnerability curves, but curves generated with centrifugation are reported to suffer from artifacts when applied to long-vesseled species. The main cause of this artifact is the issue of open vessels, resulting in a nano-particle effect that may seed premature embolism. We used two methods to test the potential mechanism behind the nano-particle effect in centrifuge-based vulnerability curves. A four-cuvette rotor system based on a traditional Cochard rotor was designed to inhibit effervescence while injecting water, but the recalcitrant vulnerability curves in Robinia could not be eliminated. There may be multiple sources, besides effervescence, of hypothetical nano-particles: they may arise from cut surfaces or they may be always present in the injected water, leading to the premature embolisms. To prevent the entry of the hypothetical nano-particles, water extraction curves in terms of PLV (percentage loss volume of extracted water from stems) vs tensions were constructed. The PLV curves of Robinia showed s-shaped characteristics after subtracting the first Weibull components from water extraction curves, which were not related to the water loss from vessels according to dye staining experiments. The differences between T 50 (xylem tension at which 50% of hydraulic conductivity is lost) in mean PLV curve and T 50 in percentage loss of conductivity curves determined by the four-cuvette rotor system and by the bench dehydration method were 3.9 MPa and 0.7 MPa, respectively. Hence, PLV curves may be a valid way to measure the cavitation resistance in long-vesseled species with centrifugation. Keeping bark intact in the process of measurement is recommended, otherwise it would increase evaporation from the entire system.